Open versus endoscopic in situ decompression in cubital tunnel syndrome: A systematic review and meta-analysis. (November 2016) - Ren, Yi-Ming; Zhou, Xian-Hu; Qiao, Hu-Yun; Wei, Zhi-Jian; Fan, Bao-You; Lin, Wei; Feng, Shi-Qing
Abstract: Objective: We conducted this systematic review and meta-analysis to compare the clinical efficacy and safety between open and endoscopic in situ decompression surgery methods for cubital tunnel syndrome (CuTS). Methods: PubMed, Medline, Embase, Cochrane Library and CNKI were searched for eligible studies. The data were extracted by two of the coauthors (WL, BYF) independently and were analyzed using RevMan statistical software, version 5.1. Relative risks (RRs) and 95% confidence intervals (CIs) were calculated. Cochrane Collaboration's Risk of Bias Tool and the Newcastle–Ottawa Scale were used to assess the risk of bias. Results: Seven studies were included for systematic review, and six studies were included for meta-analysis. The CuTS patients received open in situ decompression (OISD) or endoscopic in situ decompression (EISD). A pooled analysis of postoperative Bishop score showed that the difference was not statistically significant between the EISD group and the OISD group (RR = 0.99, 95% CI = 0.88–1.12, P = 0.88). The overall estimate of postoperative satisfaction between the EISD group and the OISD group was not found to be significant (RR = 0.98, 95% CI = 0.89–1.08, P = 0.70). The overall estimate of complications (RR = 0.88, 95% CI = 0.24–3.29, P = 0.85) suggested that the difference was not statistically significant. Conclusions: EISD and OISD for treating CuTS have equivalent efficacy for postoperative clinical improvement, whereas the incidences of complications of endoscopic surgical procedure were also same as those with the open surgical procedure. In situ decompression (especially EISD, with minor intraoperative trauma) could be treated as a valuable alternative to treat CuTS. Highlights: OISD has equal efficacy with EISD. With same complication rate, EISD intervention has same safety as OISD. EISD with minor intraoperative trauma is recommended as a valuable alternative for CuTS.